What a waste? Reflexion on social use of wastelands during pandemic - Gańko, Anna (Journal of Education Culture and Society, 2020)
Aim. The aim of the paper is to reflect on role of urban wastelands in context of legal and social construction of urban public spaces. This reflexion is based on analysis of what ecological values are connected with urban wastelands and how those values manifested during pandemic. Methods. Paper is based on observatory research put in the context of theoretical reflection on urban research, especially applying to ecology and urban management. Results. Spontaneous social animation of urban wastelands related to restrictions placed upon using green areas by Polish government in order to stop the spread of COVID-19 in April 2020 revealed potential of such places to trace regulations introduced in public spaces resulting in transfer of some social practices to less ordered and supervised areas. Conclusions. Nowadays urban wastelands gained appreciation as areas of specific high biodiversity and ecological value. However they can also be useful as a measure of social practices excluded from planned and highly organised urban places. They can be used to trace them and rethink legal and social circumstances that led to that exclusion.